The use of three-dimensional computed tomography reconstruction in the assessment of penetrating ballistic trauma - Ramasamy, A; Hinsley, D E; Brooks, A J (Emergency medicine journal : EMJ, 2009)
[...]the advantage of 3D CT reconstruction in haemodynamically stable ballistic trauma patients.